Método de quantificação da capacidade antioxidante total sérica: padronização e validação para espécie ovina - Souza, Jucilene Conceição de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The determination of total antioxidant capacity (TAC) is important to evaluation of oxidative stress, in both humans and animals. The study of methodologies to the determination of TAC has become relevant in several areas such as technology and food science, clinical laboratory, animal and human nutrition. In sheep, this determination has not yet been validated. Before starting any type of analysis, the method used for TAC measurement must be validated, since method validation is a key aspect of analytical quality assurance. Validation is a dynamic and ongoing process that begins at the stage of selection, development and optimization of the method, the quality of the tools, materials and analysts, remaining in the experimental phase. A well defined process of validation must have the characteristics investigated in the validation process to demonstrate the performance of the method as: linearity, limit of detection, limit of quantification, accuracy, precision, analytical recovery and robustness. The most commonly used method used to determine the TAC is the spectrophotometric-colorimetry assay using the (ABTS˙+) 2,2'-azinobis (3- ethylbenzthiazoline-6-sulfonate). Despite the existence of many modern techniques, the spectrophotometric method has shown to be effective, in addition to lower cost and easy handling. The method was developed, validated and standardized
Keywords: Antioxidantes; Ovino; Espectrofotometria; Estudos de validação; Stress oxidativo; Validation studies